Analisis Pengaruh Kualitas Layanan Dan Fasilitas Ekspor Terhadap Kepuasan Dan Loyalitas Pelnggan Jasa Containership Regional Container Line (RCL) Semarang - Susetyo Darmanto (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2011)
AbstractShipping companies have important roles in international trades as mediator of transportation between exporters and importers. Export volume in Tanjung Mas Semarang is increasing during 5 years, (1996-2000) while RCL Semarang as one of Shipping Company operating in Tanjung Mas Semarang facing unstable export volume due to high compation. Providing service quality and export facilities are key success factors in high competitions among shipping companies. The main objective of this research is to analyse the influence of service quality and export facilities towards customer satisfaction and customer loyality of RCL Semarang's customers. Sampels consisted 100 customers (exporters in Central Java)) of RCL Semarang, testing of empirical research using Structural Equation Modelling. The result of this study showed that service quality and export facility had signifinacant influence on customer satisfaction, and customer satisfaction had significant influence on customer loyality.